Unusual presentation of idiopathic Bell's palsy with involvement of the oculomotor nerve. Issue 9 (20th September 2022) - Bushnaq, Saji; Zafar, Atif; Silva, Floyd
Abstract : Our patient presented with symptoms consistent with Bell's palsy. The involved cranial nerves were the facial and oculomotor nerves. She had preceding upper respiratory tract infection symptoms. She had no risk factors or significant illnesses, and no other causes were found. Although there are reported cases of multiple cranial nerves affected in Bell's palsy, our review of literature revealed no prior cases of involvement of the parasympathetic oculomotor fibres in Bell's palsy.